Enhancing Students' Oral and Written Communication Skills through Discovery Learning Model: A Study on Reduction-Oxidation Reactions - Mardhatillah, Qurratun; Copriady, Jimmi; Futra, Dedi (Hydrogen: Jurnal Kependidikan Kimia, 2023)
The lack of communication skills in the learning of chemistry can negatively impact students' understanding of reduction-oxidation (redox) reactions. This study aimed to investigate the effect of the implementation of the discovery learning model on students' communication skills related to redox reactions. A quasi-experimental research design with a Non-Equivalent Control Group Design was employed. The research participants were students of class X MIPA 1 (experimental class) and class X MIPA 2 (control class) from SMA Negeri 1 Teluk Kuantan. The instrument used was a communication skills test sheet comprising five descriptive questions. The results indicated that 1) the implementation of the discovery learning model was rated as very good for each stage; 2) the writing communication skills of the experimental class were superior to those of the control class. In conclusion, the discovery learning model is an effective approach in enhancing students' communication skills on the subject of redox reactions in class X MIPA at SMA Negeri 1 Teluk Kuantan.